2022
DOI: 10.30935/conmaths/11573
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physics Lesson Planning and Teaching based on the 5Es Instruction Model in Rwanda Secondary Schools

Abstract: This research study focused on investigating the use of 5Es instructional model by physics teachers and how the model impacts the learning process of the basic concepts of electromagnetic waves in physics. In this study, six advanced-level physics teachers in four secondary schools within the Rwamagana district in Rwanda were purposively selected to participate. To collect data, 48 classroom observations were conducted, and data collected from classroom observation on the lesson delivery for all six teachers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This research has specifically revealed how inquiry-based learning makes biology more interesting and easier for students to understand biological concepts. This can specifically be seen in the inquiry-based learning method used in an experimental group of students, which is an active learning method that offers a learning environment that facilitates learners to collaborate and actively engage in their learning (Nkurikiyimana et al, 2022;Nyirahagenimana et al, 2022). This study is in agreement with other studies revealing that teaching methods that actively engage learners in biology lesson with resources improve students' attitude toward learning biology (Armbruster et al, 2010;Fančovičová & Prokop, 2008;Kisoglu, 2018;Mukagihana et al, 2021a;.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This research has specifically revealed how inquiry-based learning makes biology more interesting and easier for students to understand biological concepts. This can specifically be seen in the inquiry-based learning method used in an experimental group of students, which is an active learning method that offers a learning environment that facilitates learners to collaborate and actively engage in their learning (Nkurikiyimana et al, 2022;Nyirahagenimana et al, 2022). This study is in agreement with other studies revealing that teaching methods that actively engage learners in biology lesson with resources improve students' attitude toward learning biology (Armbruster et al, 2010;Fančovičová & Prokop, 2008;Kisoglu, 2018;Mukagihana et al, 2021a;.…”
Section: Discussionsupporting
confidence: 83%
“…Under inquiry-based learning, the 5Es educational model was pointed out as a learning cycle that improves students' attitudes toward biology. The inquiry model consists of a sequence of five interdependent phases (Nyirahagenimana et al, 2022). These are Engage, Explore, Explain, Elaborate, and Evaluate.…”
Section: Introductionmentioning
confidence: 99%
“…The 5Es instructional model was designed to stimulate observation, questioning and thinking of leaners. It is based on current understanding of learning processes and has been widely used and tested [22]. The 5Es learning cycle was appreciated to provide a room for students to hands on activities and investigation, exploring the nature which help them to grasp knowledge and learn in transferable way and hence be able to apply gained skills in everyday life [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Rwanda transitioned from French to English as a language of instruction at all levels of education 1 ; in 2012, a policy for 12 years of basic education was adopted, 2 and in 2013 the public higher education institutions were merged into a single University of Rwanda. 3 Several studies have so far documented learning of physics [4][5][6] after a competence-based curriculum was implemented in secondary schools in 2016. 7 Few people have chosen the direction of higher learning institutions.…”
Section: Introductionmentioning
confidence: 99%